Kearifan Lokal Budaya â€œNgarotâ€ dalam Usahatani Padi (Oryza Sativa) Gede Wangi (Study Kasus Di Desa Karedok Kecamatan Jatiede Kabupaten Sumedang) - Agi Dahtiar; Dety Sukmawati; Firli Muldan (Paspalum: Jurnal Ilmiah Pertanian, 2024)
Rice is a food source of energy as well as a staple food for most people, although now many people are starting to replace carbohydrates from rice with other staple foods such as potatoes, corn, sago and wheat. The aim of this research is to determine the form of local cultural wisdom "NGAROT" in the Gede Wangi rice farming business and to determine the income of farmers in the Gede Wangi rice farming business. The analytical method used in this research uses a descriptive method with a qualitative descriptive approach. The research results show that the income received by rice farmers is rice that has been milled by the respondent farmers themselves. Ngarot culture is one of the Indonesian traditional cultures, specifically in Sumedang Regency, which is still maintained and is closely related to the Sumedang Palace or the Sumedang Larang Kingdom. Ngarot culture is a community belief that they must bury buffalo heads after harvesting. Burials are carried out in the hope of bringing good things to the area and future harvests. In the midst of the rapid development of the times, local culture Ngarot was able to produce 28,800 kg of rice from 10 respondent farmers with an average cultivated land area of 5,894 mÂ², with a selling price of rice of IDR 5,500.-/ Kg. The revenue (TR/Total Revenue) received from rice farming was IDR 158,400,000. So it can be concluded that the Gede Wangi rice farming activities provide benefits for farmers, so this rice farming is worth developing.